Comparability of calibration strategies for measuring mercury concentrations in gas emission sources and the atmosphere - I. de Krom; W. Bavius; R. Ziel; E. A. McGhee; R. J. C. Brown; I. Živković; J. Gačnik; V. Fajon; J. Kotnik; M. Horvat; H. Ent (Atmospheric Measurement Techniques, 2021)
A primary mercury gas standard was developed at Van Swinden Laboratory (VSL) to establish an International System of Units (SI)-traceable reference point for mercury concentrations at emission and background levels in the atmosphere. The majority of mercury concentration measurements are currently made traceable to the empirically determined vapour pressure of mercury. The primary mercury gas standard can be used for the accurate and precise calibration of analytical systems used for measuring mercury concentrations in air. It has been especially developed to support measurements related to ambient air monitoring (1–2 ng m−3), indoor and workplace-related mercury concentration levels according to health standards (from 50 ng m−3 upwards) as well as stationary source emissions (from 1 µg m−3 upwards). The primary mercury gas standard is based on diffusion according to ISO 6154-8. Calibration gas mixtures are obtained by combining calibrated mass flows of nitrogen and air through a generator holding diffusion cells containing elemental mercury. In this paper, we present the results of comparisons between the primary gas standard and mercury calibration methods maintained by NPL (National Physical Laboratory in the United Kingdom), a National Metrology Institute (NMI), and the Jozef Stefan Institute (JSI), a Designated Institute (DI). The calibration methods currently used at NPL and JSI are based on the bell-jar calibration apparatus in combination with the Dumarey equation or a NIST (National Institute of Standards and Technology in the United States) reference material. For the comparisons, mercury was sampled on sorbent traps to obtain transfer standards with levels between 2 and 1000 ng with an expanded uncertainty not exceeding 3 % (k=2). The comparisons performed show that the results for the primary gas standard and the NIST reference material are comparable, whereas a difference of −8 % exists between results traceable to the primary gas standard and the Dumarey equation.